Evaluation of some heavy metals in water and health implications for fish consumers of the Great Cairo Sector of the Nile River - Alaa I. Khedr; Hala E. Ghannam (Scientific Reports)
Abstract Rivers serve crucial functions in the worldwide hydrological cycle. The industrial revolution, climate change, and urban development generated diverse water contaminants. This work aimed to assess the regional and seasonal distribution of some heavy metals (HMs) in the hot spot sites along the Great Cairo Sector, Nile River during 2021–2022. In addition, two commercial fish species (O. niloticus and C. gariepinus) were selected for assessing heavy metal content and human health risk. The results of heavy metals in water varied within; (1–7), (45–85.5), (19–84), (148–376), and (65–170) µg/l for Cd, Cu, Pb, Mn, and Zn, respectively over the study period. The heavy metal pollution index (HPI) results categorized the water status as unsuitable for drinking and aquatic life, but ideal for irrigation purposes. Based on Metal Index (MI) values, all examined sites were significantly at risk of metal contamination (> 1) over all uses. In the two investigated species, The results of Cd, Cu, Pb, Mn, and Zn varied in the edible part of fish species within (0.2–0.28), (2.01–5.41), (0.21–1.11), (12.1-15.25), (20.91–32.52) mg/g ww, respectively, for O. niloticus and within (0.2–0.35), (3.12–6.5), (1.52–3.62), (15.01–17.72), (15.12–26.93) mg/g ww, respectively, for C. gariepinus over the study period. The total annual daily intake of HMs was estimated to be 0.03625 and 0.03725 mg/kg.bw.day from the human consumption of O. niloticus and C. gariepinus, respectively. The Target Hazard Quotient (THQ) ranked in the order of Cd > Pb > Mn > Zn > Cu for O. niloticus and in the order of Pb > Cd > Mn > Cu > Zn for C. gariepinus with values lower than 1 that reported non-carcinogenic risk for consumers from the ingestion of investigated HMs seperately. Moreover, the Health Hazard Index (HI) slightly exceeded the threshold value of 1 of C. gariepinus, classified as moderate risk levels for consumers. Conversely, HI values were below 1 for O. niloticus, suggesting no risk from this species’ consumption. This study recommended an assertive water-quality monitoring strategy to mitigate health-related outbreaks and disruptions in aquatic ecosystems. The supplied data will undeniably assert environmental policymakers to implement sustainable pollution management and remediation measures.